Microenzymes - Mattey, Michael; Simoes, Davina; Fan, Xiaolian (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Several esterase enzymes, which are characterized by an unusually small molecular weight, have been isolated from both mesophiles (Candida lipolytica) and thermophiles (Bacillus stearothermophilus, Emericella nidulans and Talaromyces emersonnii). The Candida enzyme is 5.7 kDa, with 56 amino acid residues and the Bacillus enzyme is 1.57 kDa, with only 17 residues [1] and while both E. nidulans and T. emersonnii contained a 1.6 kDa esterase [2], Emericella also contained a 4.1 kDa enzyme. In all cases the catalytic activity appears to depend on a bound metal ion, as shown by dialysis against chelating agents, ion replacement and inhibition by metal complexing agents. Specific activities are similar to reported esterase activities. The Candida esterase has a temperature optimum of 28 oC, as might be expected from a mesophilic organism, but it has a half-life of 2 hours at 50 oC. The esterase from B. stearothermophilus is thermophilic, but whereas the optimum growth temperature is 55 oC the enzyme optimum is about 120 oC. Both enzymes (C.lipolytica and B. stearothermophilus) exhibit some substrate specificity. The Bacillus enzyme has no specificity towards the chain length of the substrate, but shows activity towards the 2- position of triglycerides. The Candida enzyme shows both chain length specificity (optimum at butyl esters), as well as specificity towards the 1- position. Keywords: - *Corresponding author: E-mail: cast@kmitl.ac.th